Pentecostal Churches’ Attitudes toward Human Trafficking in Indonesia’s Plural Society: A Socio-Legal and Interreligious Perspective - Purim Marbun; Edwin -; Josahiru Edmund Franky; Sarah Stefany; Juanda Manullang (Contemporary Issues on Interfaith Law and Society, 2026)
This study examines the institutional attitudes of Pentecostal churches in Indonesia toward human trafficking as a crime against humanity within the context of Indonesia’s religiously plural society. Situating a minority Christian denomination within majority-Muslim Java and majority-Hindu Bali, the study adopts a quantitative cross-sectional survey design involving 106 respondents—church leaders and operational actors—across five provinces: DKI Jakarta, West Java, Central Java, East Java, and Bali. Five key dimensions were measured: theological framing, church policies, operational engagement, collaboration with external stakeholders (including interreligious organizations), and gender-sensitive approaches. The analysis revealed significant provincial variation, with churches in Central Java demonstrating more organized and mature responses than those in East Java, a difference interpreted in light of each region’s distinct socio-religious dynamics. Drawing on legal pluralism, covenantal pluralism, and institutional isomorphism theory, the study reads these variations as products of inter-normative interaction among state anti-trafficking law (notably Law No. 21/2007), international human-rights norms, and the Islamic and Hindu normative orders within which the churches operate. Crucially, the study explores how interfaith cooperation with Muslim and Hindu institutions, as well as with state agencies, can optimize church responses to human trafficking. The findings are relevant to SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions). This study contributes to understanding how Pentecostal churches, as minority religious actors in a plural society, conceptualize and respond to human trafficking and provides evidence-based recommendations for strengthening interfaith collaboration, church policies, and anti-trafficking actions in plural Indonesia.